Дослідження методів захисту у хмарних системах - Назаренко, Д. М. (ХНУРЕ, 2023)
The study of protection methods in cloud systems is an important topic in the modern information technology world. Cloud systems are used to store and process large amounts of data, so security is a key aspect in their development and use. In modern cloud systems, there are various protection methods that are used to ensure the security and privacy of user data. Methods of protection in cloud systems are discussed and researched.
Keywords: хмарна система; захист у хмарних системах